2021
DOI: 10.7717/peerj-cs.698
|View full text |Cite
|
Sign up to set email alerts
|

On the classification of simple and complex biological images using Krawtchouk moments and Generalized pseudo-Zernike moments: a case study with fly wing images and breast cancer mammograms

Abstract: In image analysis, orthogonal moments are useful mathematical transformations for creating new features from digital images. Moreover, orthogonal moment invariants produce image features that are resistant to translation, rotation, and scaling operations. Here, we show the result of a case study in biological image analysis to help researchers judge the potential efficacy of image features derived from orthogonal moments in a machine learning context. In taxonomic classification of forensically important flies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
(84 reference statements)
2
3
0
Order By: Relevance
“…Our present results consolidate the findings in Goh and Khang (2021) that Krawtchouk moment invariants features extracted from whole‐image analysis of fly wing venation patterns enable a random forests classifier to produce highly accurate species identifications. Importantly, our findings have established a high accuracy lower limit (~91%) that is attainable in identification of fly species based on their wing venation patterns.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our present results consolidate the findings in Goh and Khang (2021) that Krawtchouk moment invariants features extracted from whole‐image analysis of fly wing venation patterns enable a random forests classifier to produce highly accurate species identifications. Importantly, our findings have established a high accuracy lower limit (~91%) that is attainable in identification of fly species based on their wing venation patterns.…”
Section: Discussionsupporting
confidence: 88%
“…bezziana , Chrysomya megacephala (Fabricius, 1794) (Diptera: Calliphoridae) and Chrysomya rufifacies (Macquart, 1843) (Diptera: Calliphoridae) at the species level. More recently, Goh and Khang (2021) applied a class of mathematical transformation known as Krawtchouk moment invariants onto pixel data from binarised fly wing images. They found that random forests classification of 12 fly species produced an out‐of‐bag misclassification rate of 0%, compared to about 39% using geometric morphometric data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our present results consolidate the findings in Goh & Khang [20], that Krawtchouk moment invariants features extracted from whole-image analysis of fly wing venation patterns enable a random forests classifier to produce highly accurate species identifications. Importantly, our findings have set a high lower bound for the degree of accuracy (~91%) that is attainable in identification of fly species based on their wing venation patterns.…”
Section: Discussionsupporting
confidence: 88%